Decomposition kinetics of MAX phases in extreme environments - Low, It Meng; Pang, W. (IGI Global, 2013)
MAX phases are remarkable materials but they become unstable at elevated temperatures and decompose into binary carbides or nitrides in inert atmospheres. The susceptibility of MAX phases to thermal dissociation at 1300-1550 °C in high vacuum has been studied using in-situ neutron diffraction. Above 1400 °C, MAX phases decomposed to binary carbide (e.g., TiC x) or binary nitride (e.g., TiN x), primarily through the sublimation of A-elements such as Al or Si, which results in a porous surface layer of MXx being formed Positive activation energies were determined for decomposed MAX phases with coarse pores but a negative activation energy when the pore size was less than 1.0 µm. The kinetics of isothermal phase decomposition at 1550 °C was modelled using a modified Avrami equation. An Avrami exponent (n) of < 1.0 was determined, indicative of the highly restricted diffusion of Al or Si between the channels of M6 X octahedra. The role of pore microstructures on the decomposition kinetics is discussed. © 2013, IGI Global.